2020
DOI: 10.3389/feduc.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice in Higher Education: Teacher Educators' Attitudes, Challenges, and Uses

Abstract: Teacher educators are encouraged to promote evidence-based practice in teaching and to use evidence for their own teaching. In the present study, teacher educators' attitudes, perceived challenges, and uses regarding evidence-based practice are described. Moreover, the extent to which personal factors are related to the use of evidence is investigated. In an exploratory study, 58 teacher educators from higher education participated in an online survey. The results reveal that teacher educators generally have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 62 publications
1
54
0
2
Order By: Relevance
“…Evaluation of the quality of evidence, staying up to date with the newest literature, and the need for evidencebased teaching training to bridge the gap between research and teaching practice were identified as the biggest challenges. These findings are in line with previous research in medicine (e.g., Sullivan et al, 2017) and in teacher education (Brown and Zhang, 2016;Diery et al, 2020), where environmental context and resources, skills, social influence, and professional role and identity are considered as relevant to change professionals' use of evidence into practice. Time pressure in combination with training needs and evidence evaluation seemed to be significantly more prevalent for professors than for teaching associates and school mentors.…”
Section: Discussionsupporting
confidence: 90%
“…Evaluation of the quality of evidence, staying up to date with the newest literature, and the need for evidencebased teaching training to bridge the gap between research and teaching practice were identified as the biggest challenges. These findings are in line with previous research in medicine (e.g., Sullivan et al, 2017) and in teacher education (Brown and Zhang, 2016;Diery et al, 2020), where environmental context and resources, skills, social influence, and professional role and identity are considered as relevant to change professionals' use of evidence into practice. Time pressure in combination with training needs and evidence evaluation seemed to be significantly more prevalent for professors than for teaching associates and school mentors.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, educational programmes and their associated curricula can act as a key driver for shaping healthcare professionals' knowledge, skills and attitudes towards activities associated with EBP [60]. Not surprisingly, integrating EBP into the curricula of academic programs has become an essential requirement for academic institutions providing training for healthcare professions [61][62][63].…”
Section: Barriers and Enablers For Ebpmentioning
confidence: 99%
“…Some of the teachers involved in certain research projects while some of the conduct research thesis/dissertation to acquired higher degree. Findings of the present study showed that overall use of EBP is not challenge for teachers in higher education institutions (Diery et al, 2020;MacPhail et al, 2018;Reddy et al, 2017;Loughran, 2014).…”
Section: Discussionmentioning
confidence: 51%
“…Teacher's training should enable them to use research -based evidences efficiently and to assimilate these findings with personal expertise and teaching experience. This research linkage plays important role in promoting EBP (Diery et al, 2020).…”
Section: Evidence-based Practice and Teachingmentioning
confidence: 94%